Sedimentary Setting and Ore-Forming Model in the Songtao Manganese Deposit, Southwestern China: Evidence from Audio-Frequency Magnetotelluric and Gravity Data - Lingfeng Gao (MDPI AG, 2021)
The break-up of the supercontinent Rodinia in the late Neoproterozoic led to the formation of the Nanhua rift basin within the South China Block. The Datangpo-type manganese deposit, which developed in the Nanhua rift basin, is one of the most important types of manganese deposits in South China. Although it is widely accepted that deep sedimentary structures significantly affect the manganese ore system, the relationship between the manganese deposits in South China and the Nanhua rifting process is still unclear. The origin of the manganese ore layer remains controversial. In this paper, we integrated the audio-frequency magnetotelluric (AMT) data, gravity data, and comprehensive geological and borehole data analysis to characterize the structure of the Datangpo-type manganese deposit in Songtao, Guizhou Province. The resistivity and density models produced an inclined layered structure, which correlated well with the coeval sediment strata of the Nanhua rift basin. A high-resistivity cap was observed from the surface to a depth of 800 m, corresponding to the Cambrian Loushanguan (<semantics>ϵ3−4ls</semantics>) and Palang dolomite formation (<semantics>ϵ2p</semantics>), which has helped the storage of the manganese ore. The most significant low-resistivity anomaly (25–40 Ω·m) resides at a depth of 1400 m in the Nantuo (Nh3n) gravel sandstone and Datangpo (Nh2d) silty and carbonaceous shale, corresponding to the ore-forming layer. This distinct low-resistivity layer was possibly produced by aqueous fluids and pyrite in the syn-sedimentary fault and alteration zone. The accumulations of sulfide minerals in the rock samples suggest a possible anoxic-euxinic deposition environment during the manganese mineralization and precipitation. The fault revealed in the resistivity models is perhaps a previous fault zone produced by extension in the Nanhua rifting process, which provided migration and upwelling channels for ore-forming minerals. Based on our resistivity models, density models, and geological survey, the manganese ore-forming model was derived, which can help to provide geophysical evidence for the origin of the Datangpo-type manganese deposit.